2011
DOI: 10.1128/jvi.02653-10
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Retroviral Budding Factor ALIX

Abstract: The cellular ALIX protein functions within the ESCRT pathway to facilitate intralumenal endosomal vesicle formation, the abscission stage of cytokinesis, and enveloped virus budding. Here, we report that the C-terminal proline-rich region (PRR) of ALIX folds back against the upstream domains and auto-inhibits V domain binding to viral late domains. Mutations designed to destabilize the closed conformation of the V domain opened the V domain, increased ALIX membrane association, and enhanced virus budding. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 49 publications
6
63
0
2
Order By: Relevance
“…Opening of the V domain would expose different binding sites and consequently modify the function and subcellular localization of Alix (22). This proposed model was recently corroborated by the same authors, who demonstrated that Alix activation/localization requires dissociation of the auto-inhibitory PRR and opening of the V domain arms (43). Therefore, it appears that all the substrates of Ozz identified to date, including Alix, are targeted by this protein in their assembled state and again might require Ozz binding to change conformation and/or to dissociate from their protein partners before their ubiquitination.…”
Section: Discussionsupporting
confidence: 56%
“…Opening of the V domain would expose different binding sites and consequently modify the function and subcellular localization of Alix (22). This proposed model was recently corroborated by the same authors, who demonstrated that Alix activation/localization requires dissociation of the auto-inhibitory PRR and opening of the V domain arms (43). Therefore, it appears that all the substrates of Ozz identified to date, including Alix, are targeted by this protein in their assembled state and again might require Ozz binding to change conformation and/or to dissociate from their protein partners before their ubiquitination.…”
Section: Discussionsupporting
confidence: 56%
“…6). First, Alix is anchored to sites of assembly via p6-V interactions and Bro1 seems to be unavailable to capture CHMP4, possibly due to a structural masking (45). Next, Bro1 binds NC, possibly in the budding neck, and becomes available to recruit CHMP4 during budding, a sequence of events that fits with the recent visualization of CHMP4 at the membrane once Gag assembly is complete (18).…”
Section: Discussionmentioning
confidence: 51%
“…2C). It has been proposed that the Cterminal proline-rich domain (PRD) of ALIX maintains it in an autoinhibited conformation (43,44). When the C-terminal PRD of ALIX was deleted, recruitment was strongly enhanced (Fig.…”
Section: Resultsmentioning
confidence: 99%